Pengaruh Reward Terhadap Kinerja Karyawan Pada Hasta Mulia Garut - Agnia Putri, Wahyuni; Ramayani Yusuf2 (Jurnal Manajemen dan Pemasaran, 2023)
This study aims to analyze whether there is an effect of rewards given by the company on employee performance at Hasta Mulia Garut. The research method used is descriptive and in collecting data sources using primary and secondary data sources. Data processing uses validity test, normality test, reliability test, correlation test, simple linear regression test, and coefficient of determination test using SPSS as an analysis tool. Then the data collection technique uses a questionnaire (questionnaire) and (interview) interview. The results of this study indicate that the independent variable, namely reward, has a significant and strong effect on the dependent variable, namely employee performance at Hasta Mulia Garut.